Pengaruh Gaya Kepemimpinan Partisipatif dan Iklim Organisasi Terhadap Kepuasan Kerja Guru Pada Sekolah Menengah Kejuruan (SMK) Nurul Huda Baros di Kabupaten Serang - Ice Rismawati; Ibrohim Ibrohim; Tubagus Regiasa Fajar (Amal Insani Foundation, 2023)
The purpose of this study was to determine the effect of participatory leadership style on teacher satisfaction, to determine the effect of organizational climate on teacher satisfaction and to determine the effect of participatory leadership style and organizational climate together on teacher job satisfaction at Nurul Huda Vocational High School (SMK) Baros in Serang District. This research uses a quantitative approach. As for the population in this study, there were 34 teachers at the Vocational High School (SMK) Nurul Huda Baros in Serang Regency. Saturated sampling technique is a sampling technique when all members of the population are used as samples so that the sample used in this study is 34 people. The results of this study on the first hypothesis obtained tcount > ttable (2.433 > 2.037) with a significance level <0.05 so that there is a significant influence between participatory leadership style on job satisfaction at Nurul Huda Baros Vocational School, Serang District, the second hypothesis obtained tcount > ttable (4.572 > 2.037) with a significance level <0.05 so that there is a significant influence between organizational climate on job satisfaction at Nurul Huda Baros Vocational High School, Serang Regency, the third hypothesis obtained results Fcount > Ftable (11.833 > 3.305) with a significance level <0.05 so that there is a significant influence of participatory leadership style and organizational climate on job satisfaction at Nurul Huda Baros Vocational School, Serang Regency.